2007
DOI: 10.1111/j.1365-2850.2007.01021.x
|View full text |Cite
|
Sign up to set email alerts
|

Does structured clinical supervision during psychosocial intervention education enhance outcome for mental health nurses and the service users they work with?

Abstract: This study aimed to assess whether clinical supervision provided by workplace-based supervisors can enhance outcomes for mental health nurses attending a psychosocial intervention education programme and the service users whom they work with. A quasi-experimental controlled design was used. The main outcome measure was student knowledge and attitudes towards individuals with psychosis and their caregivers. Secondary outcome measures for service users included the KGV (M) symptom scale and the Social Functionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
91
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 20 publications
4
91
0
2
Order By: Relevance
“…In some professional literature, primarily teacher, medical and nursing education, (Bradshaw, Butterworth, & Mairs, 2007;Drever & Cope, 1999;Epstein, 1999;Gale & Jackson, 1997;Lowery, 2002;Mullen & Cairns, 2001;Spouse, 2001) there is a growing body of knowledge about adult learning theory and the relationship between the expert and the novice in professional education. Currently, however, there are few theoretical or empirical perspectives in the occupational therapy literature that adequately describe the learning and skill development that take place during the supervised fieldwork experience (Bondoc, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In some professional literature, primarily teacher, medical and nursing education, (Bradshaw, Butterworth, & Mairs, 2007;Drever & Cope, 1999;Epstein, 1999;Gale & Jackson, 1997;Lowery, 2002;Mullen & Cairns, 2001;Spouse, 2001) there is a growing body of knowledge about adult learning theory and the relationship between the expert and the novice in professional education. Currently, however, there are few theoretical or empirical perspectives in the occupational therapy literature that adequately describe the learning and skill development that take place during the supervised fieldwork experience (Bondoc, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is stronger evidence for SR outcomes related to supervisee learning and development than client out comes. Positive client outcome is clearly an important goal of effective supervision and there is some promising early research in this area (Bambling, King, Raue, Sch weitzer, & Lambert, 2006;Bradshaw, Butterworth, & Mairs, 2007;White & Win stanley, 2010). The learning and professional development of the supervisee is another important outcome, and there is a growing body of evidence to support the role of the SR in supervisee satisfaction (e.g., Ladany, Ellis, & Friedlander, 1999), perceived effectiveness (e.g., Palomo et al, 2010) and skills development (e.g., Ellis & Ladany, 1997).…”
mentioning
confidence: 99%
“…However, he regarded only three of these studies as interpretable. In these three studies, the clinical outcomes reported by Watkins (2011) were depressive symptom reduction and treatment completion (Bambling et al, 2006), reductions in psychotic symptoms (Bradshaw et al, 2007), and treatment satisfaction and quality of care (White & Winstanley, 2010). These criteria overlap with current thinking on outcome criteria, which recognizes that there is ".…”
Section: Effects Of Therapy 8 Precise Clinical Outcome Evaluationmentioning
confidence: 98%